2002
DOI: 10.1063/1.1432687
|View full text |Cite
|
Sign up to set email alerts
|

Transient absorption of vibrationally excited water

Abstract: We study the spectral response of the transition between the first and the second excited state of the O–H stretch vibration of HDO dissolved in liquid D2O with two-color femtosecond mid-infrared spectroscopy. The spectral response of this transition differs strongly from the fundamental absorption spectrum of the O–H stretch vibration. In addition, excitation of the O–H stretch vibration is observed to lead to a change of the hydrogen-bond dynamics of liquid water. We show that both these observations can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 39 publications
4
76
1
Order By: Relevance
“…Bakker and co-workers used the same Lippincott-Schroeder model with the same set of parameters when they concluded that it cannot explain the asymmetry in linewidth. 39 However, they argued in terms of a classical distribution of O· · ·O distances, which for ice Ih is too small to explain the effect (in contrast to liquid water 50,51 ). In essence, it is the quantum-mechanical delocalization of the wavefunction in the R O···O direction (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Bakker and co-workers used the same Lippincott-Schroeder model with the same set of parameters when they concluded that it cannot explain the asymmetry in linewidth. 39 However, they argued in terms of a classical distribution of O· · ·O distances, which for ice Ih is too small to explain the effect (in contrast to liquid water 50,51 ). In essence, it is the quantum-mechanical delocalization of the wavefunction in the R O···O direction (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…[59][60][61][62] Also in liquid water, the 1-2 transition is broader than the 0-1 transition, and in fact it has been argued that this reflects the anharmonic coupling to the O· · ·O hydrogen the bond length. 50,51 However, due to the much larger effect of disorder in water, this effect is largely blurred. Hence it appears that ice Ih is better suited to study the quantum-mechanical character of the hydrogen bond and its consequence for vibrational spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Bulk water dynamics occur over a range of time scales, from tens of femtoseconds to several picoseconds. [15][16][17][18][19][20][21][22] These dynamics are complex and encompass elastic and inelastic interactions with the surrounding water molecules. Vibrational lifetimes, excitation transfer, dephasing and orientational correlation times are all observed to decay by ∼2 ps for bulk water.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, this notion has motivated a lot of work on the dynamical properties of bulk liquid water (1)(2)(3)(4)(5)(6)(7). However, the role of water in (bio)chemical processes is often played by a limited number of water molecules in a strongly restricted molecular environment.…”
mentioning
confidence: 99%